E-LEARNING IN ISLAMIC EDUCATION AND PANCASILA ON DURING COVID-19 PANDEMIC - Elihami Elihami (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
In the middle of the global COVID-19 epidemic, it has an influence on several sectors, including education, to ensure that e-learning Islamic education and Pancasila on during Covid-19 pandemic continues in forming the character of the nation's youngsters. The government has a policy on distant education, however there are several impediments. Teachers can continue to teach using a mixed learning paradigm, and it is believed that character development will still be ingrained. The goal of this study was to investigate the efficacy of e-learning Islamic education and Pancasila on during Covid-19 pandemic in character development of students at SD Negeri 4 Bilokka, South Sulawesi. The research approach employed is qualitative analysis. According to the conclusions of data analysis, character building is still implanted with parental supervision and reporting to school in the form of an electronic Learning Management System (LMS) of e-learning Islamic education and Pancasila on during Covid-19 pandemic, which is then confirmed by the instructor. This demonstrates how vital parents' roles at home are. More study is needed to ensure that character education can be strengthened even with different methodologies